Experimental characterization of lateral profiles of scanned proton and carbon ion pencil beams for improved beam models in ion therapy treatment planning - Schwaab, Julia; Brons, Stephan; Fieres, Johannes; Parodi, Katia (Physics in medicine and biology, 2011)
Scanned ion pencil beams carry a low-dose envelope which can extend up to several centimeters from the individual beam central axis. Depending on the energy and species of the beam, this halo consists mainly of secondary particles produced by nuclear interactions in the target or of particles undergoing multiple Coulomb scattering in the beam line components. This halo is often neglected by single Gaussian beam modeling in current treatment planning systems. One possibility of improving the accuracy of treatment planning is to upgrade the used pencil beam models by adding a description of the low-dose envelope. But at the same time it is crucial to keep the calculation time and the complexity for treatment planning in reasonable limits. As a first approach we measured the lateral beam profiles of scanned proton and carbon ion pencil beams at different energies and depths in water and air at the Heidelberg Ion Beam Therapy Center. Then we tried to describe their beam halo by adding a supplementary Gaussian function to the standard single Gauss modeling which is used at the moment by our treatment planning systems. This analysis helped to identify trends in the parameters describing the lateral beam broadening to support its modeling. Finally, it is shown that the accuracy of treatment planning could be improved by the proposed upgrade of the pencil beam model. In particular, the presented experimental data can be either used directly as input for dose calculation or serve for representative comparison with the results of calculation models such as Monte Carlo simulations for the generation of lateral basic data to be input in upgraded beam models of treatment planning systems.